The Relationship between Self Efficacy and Anxiety Facing Childbirth in Primigravid Pregnant Women - Ihsani, Aminatul; Taufik, Taufik (Current Issues in Counseling, 2023)
This research was motivated by the high maternal mortality rate (MMR) and infant mortality rate (IMR) in West Sumatra, especially in Lima Puluh Kota Regency. One of the causes of high MMR is the mother's emotional condition during pregnancy. The anxiety experienced by pregnant women is influenced by self-efficacy factors. This study aims to describe the self-efficacy and anxiety of mothers facing childbirth and examine the relationship between self-efficacy and anxiety regarding childbirth in primigravida pregnant women. This research uses quantitative methods with a correlational descriptive approach. The research sample consisted of 65 pregnant women who were selected using purposive sampling. The instruments used were a self-efficacy questionnaire with a Guttman scale model and an anxiety questionnaire with a Likert scale model. Hypothesis testing uses the Pearson product moment correlational analysis technique. The research findings are: (1) The average achievement score for self-efficacy in pregnant women is 23.19 (72.5%) which is high, (2) The average achievement score for anxiety facing childbirth is 104.72 (52.99% ) is low, (3) There is a significant negative relationship between self-efficacy and anxiety about facing childbirth with a correlation coefficient of -0.312 and a significance level of 0.011.